CONTRIBUTION AL CONOCIMIENTO DE LOS MECANISMOS DE PRODUCCION DE LOS LLAMADOS PARAERITROBLASTOS - OLAETA, R; GONZALEZ GUZMAN, IGNACIO; GALINDO MARTINEZ, G (Universidad Nacional Autónoma de Mexico, Instituto de Biología, CD MEXICO, DF, MEX, 1949)
The percentages of the various types of cells in the bone marrow of the normal rabbit were detd as an aid to future exptl study of leucocytic or erythroblastotic conditions
BOL MEN BAN REF JAL
Keywords: CONTRIBUTION, CONOCIMIENTO, MECANISMOS DE PRODUCCION, PARA ERITROBLASTOS; CIENCIAS DE LA VIDA; BIOLOGIA CELULAR; CULTIVO CELULAR